Face, Posture, And Gesture (Study of Kinesik Aspects in Qur'an) - Fairus Fairus; Syukur Kholil; Zainal Arifin (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2018)
Until now there has been no research result that comprehensively analyzes the relationship between the Qur'an and kinesik aspects as part of the realm of nonverbal communication. In fact, besides loading many terms regarding verbal communication, the Qur'an also gives a signal about the reality of nonverbal communication. One of the signs is enshrined in the Surah asa Abasa / 80 verse 1 as a Makkiyah category. The verse tells of the nonverbality of communication that Muhammad committed against a blind man named ‘Abdullah Ibn Ummi Maktum. The codification carried out by the Qur'an on the events of the past 14 centuries shows the magnitude of the Qur'an's attention to nonverbal aspects, especially kinesik, in human life. Therefore, in addition to the Surah / Abasa / 80 verse 1, it is assumed that there are also other verses that contain kinesik content both facial, gestural, and postural in the Holy Qur'an. Based on this, this study was conducted to identify which verses were revealed to Muhammad who talked about kinesik and how the verses were relevant to the development of scientific communication. From the results of the research carried out qualitatively with mix-method patterns that combine reference research (library research) and text analysis (content analysis) with thematic interpretive approaches (mauḍu'iy) it was found that the verses of the Qur'an which describe the communication process explicitly illustrates that potential kinesic aspects occur throughout the period in the process of human interaction. The Al-Qur'an contains information about kinesik processes that occur spontaneously, naturally, and conditionally. This shows that the presentation of kinesik verses is relevant to proceed in the global era, even throughout modern human life.